Overview of Adult Congenital Heart Disease and Maintainance of Optimal Function in Adult Congenital Heart Disease - James Yip (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Overview of Adult Congenital Heart Disease and Maintainance of Optimal Function in Adult Congenital Heart Disease